1991
DOI: 10.1111/j.1365-2133.1991.tb00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlations and prognosis based on hyaluronic acid serum levels in patients with progressive systemic sclerosis

Abstract: The serum levels of hyaluronic acid (sHA) were measured using an affinoimmunoenzymatic assay in patients with distal (n = 16) and proximal (n = 15) progressive systemic sclerosis (PSS) and in 31 controls. The severity of PSS was evaluated using a standardized organ-involvement score. The mean sHA was significantly higher in the patients with PSS than in controls (mean +/- SD:80 +/- 43.4 micrograms/l vs. 42.3 +/- 19.1 micrograms/l, P less than 0.001). sHA was significantly higher in patients with proximal PSS t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…High levels of HA in serum of PSS patients were pre viously reported by Levesque et al [7]. Using the affinoimmunoenzymatic assay, these authors found a positive correlation between the serum HA level and the disease severity score |7|.…”
Section: Introductionmentioning
confidence: 60%
“…High levels of HA in serum of PSS patients were pre viously reported by Levesque et al [7]. Using the affinoimmunoenzymatic assay, these authors found a positive correlation between the serum HA level and the disease severity score |7|.…”
Section: Introductionmentioning
confidence: 60%
“…In systemic sclerosis, which is characterized by an excessive accumulation of collagen in the skin and other organs, an increase of dermatan sulphate and a decrease of HYA has been reported [14][15][16]. The increase in dermatan sulphate was correlated with the clinical severity and the extent of sclerosis [14,16].…”
Section: Systemic Sclerosismentioning
confidence: 99%
“…The increase in dermatan sulphate was correlated with the clinical severity and the extent of sclerosis [14,16]. In localized scleroderma HYA is increased at the active edges of the lesions but is reduced in the centre where dermatan sulphate and chondroitin sulphate are elevated instead.…”
Section: Systemic Sclerosismentioning
confidence: 99%
“…HA levels are elevated in serum of ILD patients (12,13) and in the lung after bleomycin treatment (14 -16). CD44 participates in the activation of leukocytes and parenchymal cells in areas of inflammation, suggesting a role for CD44 in tissue remodeling and fibrosis (17,18).…”
mentioning
confidence: 99%
“…Increased deposition of interstitial HA has also been correlated with tissue function in progressive fibrosis, including ILD (12,13,23). Progressive ILD requires the generation of an invasive myofibroblast phenotype that requires TGF-␤1, where hyaluronan synthase 2 and CD44 are critical downstream components of TGF-␤1-induced fibrosis (14).…”
mentioning
confidence: 99%